Imagining Just and Empowered Futures in Harjo's Spiral to the Stars - Sarah Stanlick (The University of Alabama, 2022)
Book review of: Laura Harjo. (2019). Spiral to the Stars: Mvskoke Tools of Futurity. University of Arizona Press. 320 pages. ISBN: 978-0816541102